Métodos electroforético e inmunoquímicos para detectar proteínas de leche, soja y huevo en premezclas comerciales - Cagnasso, Carolina Elisa (2014)
The presence of milk, egg and soy proteins was evaluated in thirteen commercial products, which were premixes to make cream caramel, cake, soy “milanesas”, “tortas fritas”, pizza, gnocchi and complementary foods. Samples were analysed using SDSPAGE, immunoblotting and ELISA methods. The electrophoretic method and immunoblotting were useful to confirm the presence of milk, egg and soy proteins in four samples that declared them as ingredients. In other samples, both methods showed negative results for some of these proteins, although they were also declared as ingredients. This suggests that those proteins were not added as ingredients in these products. The ELISA kits detected very low concentration of the allergenic proteins in four products with precautionary phrases and also in five samples that made no reference to them in their labels. ELISA methods are useful to detect cross contamination due to their high sensitivity. The food industry should be responsible for the declaration of milk, egg and soy proteins in their food labels.